Diatom D18O evidence for the development of the modern halocline system in the subarctic northwest Pacific at the onset of major Northern Hemisphere glaciation - Swann, George E.A.; Maslin, Mark A.; Leng, Melanie J.; Sloane, Hilary J.; Haug, Gerald H. (American Geophysical Union, 2006)
Establishing a time frame for the development of the modern halocline and stratified water column in the subarctic North Pacific has significant paleoclimatic implications. Here we present a d18O(diatom) record consisting of only two species that represents autumn/winter conditions in the region across the onset of major Northern Hemisphere glaciation boundary. At circa 2.73 Ma a decrease in d18O(diatom) of 4.6% occurs, whereas previously published d18O(foram) results show a 2.6% increase. The d18O(diatom) and Uk37 sea surface reconstructions indicate both a significant freshening of 2–4 practical salinity units and an increase in surface temperatures in the summer to early winter period from circa 2.73 Ma onward. In contrast, the concomitant increase in d18O(foram) is likely to be reflective of conditions beneath the mesothermal structure and/or spring conditions when warmer sea surface temperatures are not present in the region. These results are consistent with the development of the modern halocline system at 2.73 Ma with year-round stratification of the water column and a strengthened seasonal thermocline during the summer to early winter period, resulting in one of the largest summer to winter temperature gradients in the open ocean. The onset of stratification would also have led to a warm pool of surface water from circa 2.73 Ma, which may have provided a potential source of extra moisture needed to supply the growing North American ice sheets at this time.